Nabonidus – Darius the Mede - Baliński, Aleksander (Anabasis. Studia Classica et Orientalia, 2019)
Nabonidus was the last ruler of the Neo-Babylonian Empire and reigned from 556 to 539 BC. However, the Book of Daniel 5:1-5:30 mentions Belshazzar, son of Nabonidus who was omitted in the biblical text, as the last native king of Babylon. The Book of Daniel 5:31 and 9:1 introduces to the sequence of the rulers an unknown Darius the Mede, who “being about threescore and two years old” began his rule after Belshazzar and became the predecessor of Cyrus II of Persia. The highlighted elderly age of the ruler allows to presume that under the name of Darius the Mede hides none other than Nabonidus. This is confirmed by Bar Hebraeus, who directly identifies Darius the Mede with Nabonidus in his Chronography (20). If Nabonidus began his rule at the age of 62, then he was born in 618/617 BC and was defeated at the advanced age of 79, in 539 BC, by Cyrus II. The reaching of such an age as determined by Psalm 90:10 is natural in the case of a man, whose mother, Adad-guppi, had lived 102 years, and died in 547/546 BC.